Can consultation skills training change doctors' behaviour to increase involvement of patients in making decisions about standard treatment and clinical trials: a randomized controlled trial. (30th June 2014) - Butow, P; Brown, R; Aldridge, J; Juraskova, I; Zoller, P; Boyle, F; Wilson, M; Bernhard, J
Abstract: Background: Informed consent is required for both standard cancer treatments and experimental cancer treatments in a clinical trial. Effective and sensitive physician–patient communication about informed consent is difficult to achieve. Our aim was to train doctors in clear, collaborative and ethical communication about informed consent and evaluate the impact of training on doctor behaviour, stress and satisfaction. Participants and Methods: Participants were 21 oncologists from 10 Australian/New Zealand (ANZ) centres and 41 oncologists from 10 Swiss/German/Austrian (SGA) centres. Oncologists were randomized to participate in a 1‐day workshop or not. Patients were recruited before and after the training. Doctors were asked to submit 1–2 audiotaped consultations before and after training. Doctors completed outcome measures before and after completing the post‐training cohort recruitment. Results: Ninety‐five consultation interactions were audiotaped. Doctors strongly endorsed the training. ANZ intervention doctors demonstrated a significant increase in collaborative communication ( P  = 0.03). There was no effect of training on other doctor behaviours. Trained doctors did not demonstrate reduced stress and burnout. Patient outcomes are presented elsewhere. Conclusions: Training can improve some aspects of the process of obtaining informed consent. Methods to increase the impact of training are required and may include longer training and more intensive follow‐up.